The Concept Of Heutagogy; The Implementation Of ‘Kurikulum Merdeka’ In Indonesia - HM, Usman; Mulyadi, Didi (CV. Inara, 2024)
When the past learning methods were carried out with traditional concepts where the teacher was the center of information, the independent curriculum offers a learner-centered learning concept. However, the quality of teachers in implementing the concept of an independent curriculum is not yet fully capable, especially by applying the concept of heutagogy. This research aims to explore the potential application of the concept of heutagogy in the context of an independent curriculum in Indonesia. This research uses the Systematic Literature Review (SLR) method, regularly collecting, critically analyzing, and presenting data and findings from various other studies. This approach is expected to make education more inclusive, relevant, competitive and improve problem-solving skills. Another objective is to evaluate the effectiveness of heutagogy in increasing learning motivation, learner engagement, preparing individuals for complex challenges in a changing society, and academic achievement in the context of an independent curriculum. The results show that the implementation of the heutagogy concept in the independent curriculum gives learners more control over the learning process, and fosters greater independence, creativity and engagement. Thus, the concept of heutagogy is not only a valuable addition in the context of an independent curriculum, but also a strong foundation for creating a more inclusive and competitive education system in Indonesia. Through the heutagogy approach, individuals are expected to develop lifelong learning skills and become active agents of change in building a brighter and more sustainable future. Book Antiqua 10, single space.